Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To determine which ordered pair is a solution to the equation:
[tex]\[ -4x + 7 = 2y - 3, \][/tex]
we will substitute the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] from each ordered pair into the equation and check if the equality holds.
### Step 1: Test the pair [tex]\((2, 1)\)[/tex].
Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 1\)[/tex] into the equation:
[tex]\[ -4(2) + 7 = 2(1) - 3. \][/tex]
Now compute each side of the equation:
[tex]\[ -4 \cdot 2 + 7 = -8 + 7 = -1, \][/tex]
[tex]\[ 2 \cdot 1 - 3 = 2 - 3 = -1. \][/tex]
Since [tex]\(-1 = -1\)[/tex], the pair [tex]\((2, 1)\)[/tex] satisfies the equation.
### Step 2: Test the pair [tex]\((5, -5)\)[/tex].
Substitute [tex]\(x = 5\)[/tex] and [tex]\(y = -5\)[/tex] into the equation:
[tex]\[ -4(5) + 7 = 2(-5) - 3. \][/tex]
Now compute each side of the equation:
[tex]\[ -4 \cdot 5 + 7 = -20 + 7 = -13, \][/tex]
[tex]\[ 2 \cdot (-5) - 3 = -10 - 3 = -13. \][/tex]
Since [tex]\(-13 = -13\)[/tex], the pair [tex]\((5, -5)\)[/tex] also satisfies the equation.
### Conclusion:
Both ordered pairs, [tex]\((2, 1)\)[/tex] and [tex]\((5, -5)\)[/tex], are solutions of the equation. Therefore, the correct answer is:
[tex]\[ \boxed{\text{Both } (2,1) \text{ and } (5,-5)} \][/tex]
So, the answer is (C) Both [tex]\((2,1)\)[/tex] and [tex]\((5,-5)\)[/tex].
[tex]\[ -4x + 7 = 2y - 3, \][/tex]
we will substitute the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] from each ordered pair into the equation and check if the equality holds.
### Step 1: Test the pair [tex]\((2, 1)\)[/tex].
Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 1\)[/tex] into the equation:
[tex]\[ -4(2) + 7 = 2(1) - 3. \][/tex]
Now compute each side of the equation:
[tex]\[ -4 \cdot 2 + 7 = -8 + 7 = -1, \][/tex]
[tex]\[ 2 \cdot 1 - 3 = 2 - 3 = -1. \][/tex]
Since [tex]\(-1 = -1\)[/tex], the pair [tex]\((2, 1)\)[/tex] satisfies the equation.
### Step 2: Test the pair [tex]\((5, -5)\)[/tex].
Substitute [tex]\(x = 5\)[/tex] and [tex]\(y = -5\)[/tex] into the equation:
[tex]\[ -4(5) + 7 = 2(-5) - 3. \][/tex]
Now compute each side of the equation:
[tex]\[ -4 \cdot 5 + 7 = -20 + 7 = -13, \][/tex]
[tex]\[ 2 \cdot (-5) - 3 = -10 - 3 = -13. \][/tex]
Since [tex]\(-13 = -13\)[/tex], the pair [tex]\((5, -5)\)[/tex] also satisfies the equation.
### Conclusion:
Both ordered pairs, [tex]\((2, 1)\)[/tex] and [tex]\((5, -5)\)[/tex], are solutions of the equation. Therefore, the correct answer is:
[tex]\[ \boxed{\text{Both } (2,1) \text{ and } (5,-5)} \][/tex]
So, the answer is (C) Both [tex]\((2,1)\)[/tex] and [tex]\((5,-5)\)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.